ANALISIS PROFITABILITAS, TINGKAT PERTUMBUHAN, UTANG, DAN NILAI PERUSAHAAN - Lydia, Lydia (Media Akuntansi dan Perpajakan Indonesia, 2020)
A company has a goal to increase the value of the company. Anincrease in company value results in an increase in shareholder welfare. Asan investor, of course investors will choose to invest in companies with agrowing company value. Company value can be influenced by profitability,company growth, leverage, and company size. The purpose of this studywas to determine the effect of profitability, company growth, and corporateleverage by using company size as a control variable. This research focuseson the manufacturing industry especially the food and beverage sub-sectorlisted on the Indonesia Stock Exchange in 2014–2018. This study uses quantitativeresearch with a total sample of 14 companies and each companyuses five data so that the total data is 70 data. This study uses multiplelinear regression analysis processed by the SPSS program. The results showedthat profitability, company growth, and corporate leverage have a significantinfluence on firm value. Profitability is the variable with the highestinfluence which is then followed by company growth and corporate leverage.